Perlocutionary Acts in the movie "Dead Poets Society" - Netta, Ayuna; Aufar, M. Fadhil; Farsia, Lina; Sarair, Sarair (ACCENTIA: Journal of English Language and Education, 2022)
This study aims to analyze the perlocutionary acts used by the main character of Dead Poet Society, Mr. Keating, towards his students. The study employed the qualitative approach, examining the data from Mr. Keatings words and actions. The study then analyzed the data by classifying the speech acts, on the aspect of perlocutionary acts, and also comparing the speech acts to the actions and the values in the movie Dead Poets Society. The findings of the study revealed that Mr. Keating frequently used the perlocutionary acts to inspire and motivate the students. Therefore, he used a variety of teaching methods in his class in order to continuously encourage and motivate his students to work toward their aspirations.